Parental Attitudes About Childhood Vaccination: Factors And Trends In Rawalpindi - Mughal, Fatima Ali Raza; Naeem, Tabinda; Zulfiqar, Shaista; Zaidi, Nosheen (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the frequency of complete vaccination of children according to the EPI schedule and to assess the contributing factors for missing vaccines among parents of children under 12 years of age attending the Paediatric OPD of FFH, Rawalpindi. Methods: This cross-sectional study was conducted at the Paediatric OPD of a tertiary care hospital by investigators from the Department of Community Medicine from March 2022 to May 2022, involving parents of children under 12 years of age. A total of 320 participants took part in the study. After obtaining approval from the institutional ethics review committee, data were collected using non-probability consecutive sampling. Parents' Attitudes towards Childhood Vaccinations, a pre-validated tool, was used as an instrument with permission from the developer. Data was analysed using SPSS version 26. Results: Among total respondents, 83.8% had fully vaccinated children, and 72.8% never delayed their child’s vaccination. 38.1 % of the parents were concerned about the side effects of the vaccine, while 56.3% had no hesitancy regarding childhood vaccines. 53.7% respondents agreed that the child’s vaccination as per the EPI schedule was good. There was a statistically significant association with the level of education (p= 0.001) and ethnicity (p= 0.001) of the respondent with the delayed vaccination of the child. Conclusion: Our study found that while most of the respondents’ children were fully vaccinated according to the EPI schedule, several parents had concerns about the safety and efficacy of the vaccines. We also discovered that the education level of the child’s parent or guardian and their ethnicity were significantly associated with delay in vaccinating the child. The public health implications point towards greater health education and health promotion in all areas of the country.